Preservation of Bacillus pumilus PU4-2 xylanases by immobilization technique into pollard and cation addition - Haryati, T; Marbun, P.A; Purwadaria, T (Indonesian Journal of Animal and Veterinary Sciences, 2010)
Utilization of by-product from agriculture as alternative source of feedstuff has been widely practiced. However their usage is limited due to high fiber content and low nutrient digestibility. The use of specific hydrolizing enzymes, xylanases are gaining importance because of their wide application in various industrial sectors especially in bioconversion of hemicellulosic material. This experiment was done to evaluate the effect of cation addition and immobilization of enzyme into pollard on stability of B. pumilus xylanase. The enzyme extract was purified by precipitation with 75% ammonium sulphate. Four kinds of cation (Ca2+, Fe3+, Mg2+, Zn2+) were added to the purified enzyme, at concentration of 1m M and stored at 4 and 27ËC. For immobilization process, the optimum enzyme concentration that will be added to pollard has been evaluated by analysis of xylanase activity and their recovery. The specific activity of enzyme after precipitation increased 1.8 times, from 420.3 to 765.2 U/mg protein. All cations act as activator which relative activity become 130.6; 139.0; 103.8 and 163.5% respectively. Concentration of 0.5mM Ca2+ and Fe3+ were most able to keep xylanases activity stable at 4ËC. The optimum composition of enzymes and pollard was 1.5 ml for 5 gram of pollard with recovery of xylanases activity of 82.2%. In immobilized enzyme, the activity of enzyme without cation addition is higher than that with addition of Ca2+ and Fe3+. Activity of enzyme stored at 4ËC is more stable than that at 27ËC. Immobilized enzyme is more stable for storage, which lasted for 7 weeks at 27ËC and 12 weeks at 4ËC compared to liquid enzyme which lasted for only 7 days at 27ËC and 13 days at 4ËC. Key words: Xylanase, Bacillus pumilus PU4-2, Preservation, Imobilization, Cation